2017
DOI: 10.31231/osf.io/4bjds
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meditation Experience Predicts Introspective Accuracy

Abstract: The accuracy of subjective reports, especially those involving introspection of one's own internal processes, remains unclear, and research has demonstrated large individual differences in introspective accuracy. It has been hypothesized that introspective accuracy may be heightened in persons who engage in meditation practices, due to the highly introspective nature of such practices. We undertook a preliminary exploration of this hypothesis, examining introspective accuracy in a cross-section of meditation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
(25 reference statements)
1
22
0
Order By: Relevance
“…As predicted, however, meditators scored higher than controls on the Body Awareness subscale of the Scale of Body Connection and that these scores were related in a graded fashion to task performance (time and score) before the nap. These finding are consistent with studies suggesting that sustained meditation practice contributes to higher levels of somatic awareness [8] and confirms our rationale for choosing a full-body balance task to examine patterns of sleep-dependent memory consolidation. In this case, one required skill for learning the task quickly is a heightened level of attunement to one's own bodily/somatic states.…”
Section: Task Performance Body Awareness and Bodily Dissociationsupporting
confidence: 91%
See 1 more Smart Citation
“…As predicted, however, meditators scored higher than controls on the Body Awareness subscale of the Scale of Body Connection and that these scores were related in a graded fashion to task performance (time and score) before the nap. These finding are consistent with studies suggesting that sustained meditation practice contributes to higher levels of somatic awareness [8] and confirms our rationale for choosing a full-body balance task to examine patterns of sleep-dependent memory consolidation. In this case, one required skill for learning the task quickly is a heightened level of attunement to one's own bodily/somatic states.…”
Section: Task Performance Body Awareness and Bodily Dissociationsupporting
confidence: 91%
“…Mindfulness interventions, including sitting meditation practices and movement-based practices such as yoga or t'ai chi [5], all include an element of cultivating access to and awareness of increasingly subtle bodily sensations [6,7]. Meditation practitioners, therefore, may represent an 'expert' group of healthy individuals who intentionally cultivate attention to bodily states, and are better able to access and employ them [8]. Meditators may embody cognitive processes differently than do non-meditators; in particular, they may rely more upon awareness of kinesthetic and other types of endogenous information to encode memories.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical findings to support this claim are mixed. Although studies that assessed performance on a heartbeat detection task -a standard measure of interoceptive awareness -found no evidence that meditators had superior performance to non-meditators 124,125 , other studies found that meditators showed greater coherence between objective physiological data and their subjective experience in regard to an emotional experience 126 and the sensitivity of body regions 127 .…”
Section: Box 3 | Mindfulness Meditation As Exposure Therapymentioning
confidence: 98%
“…Furthermore, insula activation correlates with interoceptive accuracy when participants monitor their heartbeat (Critchley, Wiens, Rotshtein, Ohman, & Dolan, 2004). Notably, meditation training is associated with greater interoceptive accuracy (Fox et al, 2012) and is associated with changes in insula structure and function (Farb, Segal, & Anderson, 2013;Fox et al, 2014;Young et al, 2017). The mid and posterior insula have a close relationship with sensorimotor cortices, which may also play a role in representing the concrete aspects of sensory experience during emotional processing (Khalsa, Rudrauf, Feinstein, & Tranel, 2009;Satpute et al, 2015).…”
Section: Introductionmentioning
confidence: 99%